A Critical Review of “Ijtehadic Paradigm of Religious Science” - SayyedMohammadTaghi Movahed Abtahi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Ijtehadic Paradigm of Religious Science is an influential book in the field ofreligious science. According to the potentials and limitations of the concept ofparadigm in Kuhn's philosophy of science, and compared with other terms suchas school and doctrine, as well as other variables including ontology, epistemology, anthropology, and methodology  in the literature of Hawzah, the authors have redefined theparadigm and presented their theory based on this new definition.In the "Ijtehadic Paradigm of Religious Science" they have attemptedto show that the results of Ijtehadic method are valid and consideredas knowledge. Moreover, they have shown how to use different resources andmethods coherently. In this paper, different aspects of the book are reviewed in the light of a critical approach.